PERAN INTERNASIONAL COMMITTEE OF THE RED CROSS (ICRC) DALAM MENANGANI KORBAN KONFLIK BERSENJATA INTERNASIONAL DI AFGHANISTAN TAHUN 2016-2021 - Febriana Putri Sari; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research analyzes how International Committee of The Red Cross (ICRC) do their role to handle the victims of international armed conflict in Afghanistan that occurred in the periode of 2016 – 2021. This international armed conflict that happened in Afghansitan caused much victims from both of civilian and military sides. ICRC as an organization that engaged in the humanitarian field certainly can not remain silent about this situations that has claimed many lives as victims. As an unique international organization, ICRC take reaction to respond the situation that are considered as an emergency regarding humanity and human security based on humanitarian diplomacu concept, which is to protect the existence of every society and protect them from every forms of violence. This research uses qualitative method. Data collection techniques through literature studies sourced from several books, journal, articles and official websites. This research uses the pluralism prespective and the concept of humanitarian diplomacy. The results from this research showed that ICRC as an organization with humanity principles have did several roles that important to handled and protect the rights and security of every victims caused of international armed conflict in Afghanistan. These aids are in form of assistances for food needs, improvement of health facilities and medical personnel, rehabilitation facilities for people with disabilities, rebuild the economiy and also diplomatic assistances to solve the conflict and create peace. Keyword : international armed conflict, humanitarian diplomacy, ICRC